Health-related quality of life results from the IFM 2009 trial: treatment with lenalidomide, bortezomib, and dexamethasone in transplant-eligible patients with newly diagnosed multiple myeloma. Issue 6 (11th May 2020) - Roussel, Murielle; Hebraud, Benjamin; Hulin, Cyrille; Perrot, Aurore; Caillot, Denis; Stoppa, Anne-Marie; Macro, Margaret; Escoffre, Martine; Arnulf, Bertrand; Belhadj, Karim; Karlin, Lionel; Garderet, Laurent; et al.
Abstract: The Intergroupe Francophone du Myelome 2009 trial (NCT01191060) assessed health-related quality of life (HRQoL) in patients with newly diagnosed multiple myeloma (NDMM) receiving lenalidomide/bortezomib/dexamethasone (RVd) induction therapy followed by consolidation therapy with either autologous stem cell transplantation (ASCT) plus RVd (RVd-ASCT) or RVd-alone; both groups then received lenalidomide maintenance therapy for 1 year. Global HRQoL, physical functioning, and role functioning scores significantly improved for both cohorts from baseline to the end of consolidation and were sustained during maintenance and follow-up, with clinically meaningful changes (RVd-alone: p = .0002; RVd-ASCT: p < .001). Similarly, both groups showed clinically meaningful improvements from baseline in fatigue, pain, and disease symptom scores. Side effects of treatment scores remained stable. In the RVd-ASCT group, there was transient worsening in HRQoL immediately after ASCT. These findings suggest that the clinical improvements observed with RVd-based treatment are accompanied by overall improvements in HRQoL for patients with NDMM.